Teorije o elitah - Atanasovski, Gligor (Teorija in praksa, 1997)
The classic elitist theory is renowned among Italian po1itical schools and it is the continuity of Machiavelli's tradition. Two of the most famous thinkers are Gaetano Mosca and Vilfredo Pareto. This text answers three questions: Who governs or rules in the political society, what are the characteristics of the elites, and how does one become a member of the elites? Elitist theory is not a mythical category.
Keywords: elite; teorija elit; politična elita; politična filozofija; družbena diferenciacija